1996
DOI: 10.5453/jhps.31.41
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Concentrations of Metal Elements in Various Organs of the Mouse following Multiple Intraperitoneal Administration of Ca-DTPA.

Abstract: This study was conducted to investigate the effect of diethylenetriaminepentaacetic acid (DTPA) on the concentrations of some metal elements in mouse organs to accumulate fundamental knowledge on its pharmacological properties and its side effects. DTPA was injected intraperitoneally into C3H/He mice 3 times per week at a dose of 0.3mmol per kg body weight, and the concentrations of 13 metal elements in the liver, spleen kidneys, lungs, femur and serum were measured by inductively coupled plasma emission spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Brain and liver metal levels measured in the present study were comparable to previously reported measurements in mouse and rat tissues (SATO et al 1996 ; Schneider et al 2014 ; Garza-Lombó et al 2018 ). In our analysis, within a tissue, metal concentrations generally correlated positively, but negatively with the mass of the tissue sample.…”
Section: Resultssupporting
confidence: 92%
“…Brain and liver metal levels measured in the present study were comparable to previously reported measurements in mouse and rat tissues (SATO et al 1996 ; Schneider et al 2014 ; Garza-Lombó et al 2018 ). In our analysis, within a tissue, metal concentrations generally correlated positively, but negatively with the mass of the tissue sample.…”
Section: Resultssupporting
confidence: 92%